Bean School, Wabaunsee County - Schendt, Jamie (Kansas State University, The Chapman Center for Rural Studies, 2008)
Jamie Schendt writes a history of Bean School (District #3 one room school) in Wabaunsee County. Serving an integrated landscape of both white and African American farmers, Bean School was attended by Washington Owen, first black graduate of KSU. The author shows that Bean school played many roles in the community, including a shared Bible Study forum sometimes led by African American farmers. Early photographs of the school and plat maps are included.
Jamie Schendt, “Bean School, Wabaunsee County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/11.
Keywords: Alma; Bean School; Exodusters; African American; District School #3; Integration